Cosmotellurism in Lombroso’s work - Ciliberti, Rosagemma; Licata, Marta; Tesi, Chiara; Fusco, Roberta; Armocida, Giuseppe (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Few know that Lombroso was also involved in epidemiological research. In particular, Lombroso’s scientific reflections on Medical Geography were addressed to the theme of climate influences and meteorological conditions on human conduct. The authors analyze the scientific production and the works of Lombroso devoted to medical geography. Discussion: Lombroso carried out accurate epidemiological investigations using the statistical method with great modernity, combining health data with geographical and climatic data to demonstrate the relationship between man, the environment and health in a social vision of preventive and curative medicine. Conclusions: The theory of Cosmotellurism in Lombroso’s work is not only a source of unquestionable interest in the History of Medicine. The heritage of Medical Geography within the pre-bacteriological medical culture can continue with its teachings to correctly address the clinician’s thinking even in the current historical context in which endemic and epidemic pathologies re-emerge in various parts of the world. (www.actabiomedica.it)